“Entre ‘Femme noire’ de Senghor et Femme nue, femme noire de Beyala: réseau intertextuel de subversion et d’échos” - Asaah, A.H. (French Forum 3(32):107-122, 2007)
Many scholars object to Senghor’s idealization of the Black woman and the African past. « Femme noire », which is Senghor’s most famous poem, epitomizes this stereotyping impulse. Even if Beyala sets out in her novel, Femme nue, femme noire, to parody Senghor’s poem, it bears noting that her transgression nonetheless reveals her indebtedness to the poet. This article attempts to study the dual relationship of dissonance and consonance between the two texts in light of the concept of intertextuality.
Keywords: Black Woman; Nudity; Senghor; Beyala; Intertextuality; Hypotext; Hypertext; Subversion; Echoes